2020
DOI: 10.3390/cancers12071913
|View full text |Cite
|
Sign up to set email alerts
|

The LIM Protein Ajuba Augments Tumor Metastasis in Colon Cancer

Abstract: Colorectal cancer, along with its high potential for recurrence and metastasis, is a major health burden. Uncovering proteins and pathways required for tumor cell growth is necessary for the development of novel targeted therapies. Ajuba is a member of the LIM domain family of proteins whose expression is positively associated with numerous cancers. Our data shows that Ajuba is highly expressed in human colon cancer tissue and cell lines. Publicly available data from The Cancer Genome Atlas shows a negative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…Moreover, when monocytic cells switch from a proliferative to a differentiated state, Ajuba expression was reduced. Previous data from our lab demonstrated that knockout of Ajuba using CRISPR/Cas9 resulted in non-viable HCC cell lines [40]. This observation, together with the embryonic lethality of CRISPR/Cas9 KO animals has also been supported by Loganathan et al [49], and that Ajuba expression was found during embryogenesis in all embryonic germ layers and within fetal components of the developing placenta [50,51].…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, when monocytic cells switch from a proliferative to a differentiated state, Ajuba expression was reduced. Previous data from our lab demonstrated that knockout of Ajuba using CRISPR/Cas9 resulted in non-viable HCC cell lines [40]. This observation, together with the embryonic lethality of CRISPR/Cas9 KO animals has also been supported by Loganathan et al [49], and that Ajuba expression was found during embryogenesis in all embryonic germ layers and within fetal components of the developing placenta [50,51].…”
Section: Discussionsupporting
confidence: 68%
“…This AJUBA‐induced YAP increase permits regulation of cyclin D1, Bcl‐xL and GLUT1, influencing mitochondrial potential and glucose uptake to increase cell growth and chemoresistance 105 . Additionally, AJUBA induces metastatic colon cancer by promoting migratory pathways in human colon cancer cells such as Smad1 induced AJUBA/Snail binding to downregulate E‐cadherin expression 106,107 . Furthermore, AJUBA functions as a co‐activator to promote proliferation in pancreatic and breast cancer with the transcription factor SP1 via a feed‐forward loop of downstream targets, EGFR and IGF1R 108 and with ERα by recruiting DBC1 and CBP/p300 to induce expression of TFF1, Greb1 and SGK3 (ERα target genes), 109 respectively.…”
Section: Ajuba’s Role In Cancer Stem Cells Of Epidermal Cancersmentioning
confidence: 99%
“…As a scaffolding protein, AJUBA plays an essential role in oncogenesis by regulating major signaling pathways, such as Wnt, JAK/STAT, RAS/ERK, and Hippo. It stabilizes adhesion junctions by linking cadherin and α-catenin to cytoskeletal receptor complexes [71] . AJUBA/SP1 forms an SP1 activating feed-forward loop that functions as a biomarker for pancreatic cancer [18] .…”
Section: Discussionmentioning
confidence: 99%